Assessment of Oxidative Stress Markers in Hypothermic Preservation of Transplanted Kidneys - Karol Tejchman; Anita Sierocka; Katarzyna Kotfis; Maciej Kotowski; Barbara Dolegowska; Marek Ostrowski; Jerzy Sienko (MDPI AG, 2021)
Ischemia-reperfusion injury (IRI) after renal transplantation is a complex biochemical process. The first component is an ischemic phase during kidney storage. The second is reperfusion, the main source of oxidative stress. This study aimed to analyze the activity of enzymes and concentrations of non-enzymatic compounds involved in the antioxidant defense mechanisms: glutathione (GSH), glutathione peroxidase (GPX), catalase (CAT), superoxide dismutase (SOD), glutathione reductase (GR), glutathione transferase (GST), thiobarbituric acid reactive substances (TBARS), malondialdehyde (MDA), measured in preservation fluid before transplantation of human kidneys (KTx) grafted from brain dead donors. The study group (N = 66) was divided according to the method of kidney storage: Group 1-hypothermic machine perfusion (HMP) in LifePort perfusion pump, n1 = 26, and Group 2-static cold storage (SCS), n2 = 40. The measurements of kidney function parameters, blood count, and adverse events were performed at constant time points during 7-day hospitalization and 3-month follow-up. Kidney perfusate in Group 2 was characterized by significantly more acidic pH (p < 0.0001), higher activity of GPX [U/mgHb] (p < 0.05) and higher concentration of MDA [μmol/L] (p < 0.05). There was a statistically significant improvement of kidney function and specific blood count alterations concerning storage method in repeated measures. There were aggregations of significant correlations (p < 0.05) between kidney function parameters after KTx and oxidative stress markers: diuresis & CAT, Na+ & CAT, K+ & GPX, urea & GR. There were aggregations of significant correlations (p < 0.05) between recipient blood count and oxidative stress markers: CAT & MON, SOD & WBC, SOD & MON. Study groups demonstrated differences concerning the method of kidney storage. A significant role of recipient's gender, gender matching, preservation solution, and perfusate pH was not confirmed, however, basing on analyzed data, the well-established long-term beneficial impact of HMP on the outcome of transplanted kidneys might partially depend on the intensity of IRI ischemic phase and oxidative stress, reflected by the examined biomarkers.